The Law of Circumcision for Women According to The Syafi'i Mazhab, Maqosidus Sharia, and Constitution - Husni Mubarok; M. Jamil; Akmaluddin Syahputera; Adnan Ahmed Usmani (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2023)
The implementation of self-circumcision in Indonesia was sheltered by the government, in this case, the Ministry of Health, in 2010 with the issuance of Regulation of the Minister of Health of the Republic of Indonesia Number 1636/MENKES/PER/XI/ 2010 concerning Female Circumcision. Problems arose when the 2010 rule was repeated in 2014, resulting in discomfort among the people of Marbau District, North Labuhanbatu Regency. This study will analyze the enlightenment of the theory of legal certainty, maqashid asy-syari'ah, regarding Circumcision in the Regulation of the Minister of Health of the Republic of Indonesia Number 6 of 2014 in Marbau District, North Labuhanbatu Regency. The research method used the library (library research) and (empirical research). The Primary sources are observations, interviews, and Regulations of the Minister of Health in 2010 and 2014. The research results show that in terms of legal certainty theory, the Law is made so that it can be implemented by the community, while The 2014 repeal regulation is uncertain because it is difficult to implement. In the maqashid asy-shari'ah aspect, Circumcision is part of religious care (hifzud din), on the other hand, it does not mean that in the practice of Circumcision, harming girls or neglecting to protect oneself or one's soul (hifzhun nafs), but for the sake of giving obedience, and it is useful to control the lust of a girl when she grows up. Pelaksanaan khitan sendiri di Indonesia telah dinaungi oleh pemerintah dalam hal ini Kementerian Kesehatan pada tahun 2010 dengan dikeluarkannya Peraturan Menteri Kesehatan Republik Indonesia Nomor 1636/MENKES/PER/XI/2010 tentang Sunat Perempuan. masalah muncul ketika aturan pada tahun 2010 ini dicabut pada tahun 2014, sehingga terjadi kegelisahan di tengah masyarakat Kecamatan Marbau Kabupaten Labuhanbatu Utara. Penelitian ini akan menganalisis tinjauan teori kepastian hukum, maqashid asy-syari`ah tentang Khitan dalam Peraturan Menteri Kesehatan Republik Indonesia Nomor 6 Tahun 2014 di Kecamatan Marbau Kabupaten Labuhanbatu Utara. Metode penelitian yang digunakan adalah pustaka (library research) dan (empirical research). Sumber primer, terdiri dari hasil observasi, dan wawancara, Peraturan Menteri Kesehatan tahun 2010, dan tahun 2014. Hasil penelitian menunjukkan bahwa pada aspek teori kepastian hukum, hukum dibuat agar dapat dijalankan oleh masyarakat, sedangkan pencabutan aturan tahun 2014 tersebut menjadi suatu hal yang sifatnya tidak pasti, karena sulit dijalankan. Pada aspek maqashid asy-syari`ah, Khitan adalah bagian dari penjagaan agama (hifzud din), sebalik itu bukan berarti dalam praktik khitan mencelakai anak perempuan atau mengabaikan menjaga diri atau jiwa (hifzhun nafs), tapi demi memberikan kehormatan, dan bermanfaat mengontrol nafsu anak perempuan itu ketika dewasa